HUBUNGAN PENGUASAAN KOSAKATA DENGAN KETERAMPILAN MENULIS KARANGAN DESKRIPTIF BAHASA JERMAN SISWA - Hasrar Hasrar; Ambo Dalle; Misnawaty Usman (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2018)
The purpose of the study was to know the relationship between vocabulary mastery with a descriptive essay writing skills of language Germany. Data was collected using writing skill test. Data were analyzed through the Product Moment correlation. The population of this research is the grade XI IPA which consisting of 1 class, numbered 20 people. The sample was selected using the technique of  Total Sampling namely whole grade XI IPA that add up to 20 students. The results of this study showed that there is a significant relationship between vocabulary mastery with a descriptive essay writing skills of language Germany grade XI IPA SMA Karya Sahari Bulukumba (rh = 0,609 > rt = 0,444).